2019
DOI: 10.1039/c9an00480g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of disease biomarkers using an immuno-wall device with enzymatic amplification

Abstract: We present a fluorometric sandwich immunoassay for biomarkers utilizing an antibody-modified microfabricated wall and antibody labeled with an enzyme for signal amplification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Our previous research has suggested that DDAO molecules could be accumulated inside the wall and could efficiently magnify the fluorescence intensity. 32 First, a standard solution of H5-HA in PBS (20 ng/mL) was used as a model to probe the fluorescence intensity variation during 30 min. It was found that the fluorescence intensity considerably increased as a function of time (Figure 4a), and the value of the signal/blank ratio (S/B) because of the DDAO accumulation inside the immunowall was slightly improved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous research has suggested that DDAO molecules could be accumulated inside the wall and could efficiently magnify the fluorescence intensity. 32 First, a standard solution of H5-HA in PBS (20 ng/mL) was used as a model to probe the fluorescence intensity variation during 30 min. It was found that the fluorescence intensity considerably increased as a function of time (Figure 4a), and the value of the signal/blank ratio (S/B) because of the DDAO accumulation inside the immunowall was slightly improved.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the sensitivity, an enzyme label was used, and the signal was amplified by the enzymatic reaction with a fluorogenic substrate. 32…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides portability, sensitivity of the method is important to detect low-concentrated biomarkers. Tokeshi and co-workers presented very sensitive immunoassays for disease biomarkers, where the capture antibodies are immobilized at the channel walls to improve the limit of the detection …”
Section: Selected Applications In Bioanalysis and Diagnosticsmentioning
confidence: 99%
“…Tokeshi and co-workers presented very sensitive immunoassays for disease biomarkers, where the capture antibodies are immobilized at the channel walls to improve the limit of the detection. 176 Extracellular Vesicles (EV). Exosomes secreted by cells are considered as valuable biomarkers to diagnose various diseases, such as cancer, as well as potential drug delivery vehicles.…”
mentioning
confidence: 99%